A physical symptom-based measure of quality of care for children affected by HIV/AIDS. Issue 3 (3rd July 2019) - Qiao, Shan; Li, Xiaoming; Zhao, Guoxiang; Zhao, Junfeng; Kamat, Deepak
ABSTRACT: Based on cross-sectional data of 1, 625 children aged 6–18 years who were affected by parental HIV/AIDS in central rural China, we evaluated a physical symptom-based measure of the quality of care (QOC_PS) for these children. The QOC_PS has acceptable reliability estimates for children of both genders, at a different ages, and by orphanhood status. Known-group validation and construct validity analysis demonstrated a good validity of QOC_PS indicator. The QOC_PS score was significantly associated with psychosocial well-being measures among children. The physical symptom-based measure provides a psychometrically appropriate indicator of quality of care for children affected by HIV/AIDS in China. It could be used as an alternative measure to assess the quality of care in resource-poor settings where other objective measurements are not available or feasible. Future research is needed to further validate the scale among children in different living environments across various cultural settings.